COMMUNITY SERVICE IN CATTLEMANS GROUP BY MAKING FERMENTED ANIMAL FEED (SILAGE) IN SIDOREJO, UMBULSARI, JEMBER DISTRICT - Nidya Shara Mahardika; Andi Eko Wiyono; Jani Januar (UNEJ e-Proceeding, 2022)
Sidorejo Village, Umbulsari District, has the potential for animal husbandry. Villagers on average have cattle and goats which can be developed as a driving force for the village economy. The biggest need in the development of animal husbandry is the adequacy of animal feed. Therefore, based on the results of field observations and discussions, the problem faced by breeders is a lack of knowledge and understanding of breeders about good farming practices. The second problem is the low skill of breeders in making fermented animal feed. Therefore it is necessary to empower breeders group in collaboration with related institutions to overcome various existing problems. This solution is expected to be able to develop the potential of existing breeders in Sidorejo Village through the "One Lecturer One Village" community service program. The results achieved from this activity were: 1) 80 percent of breeders have understood the training material on making fermented animal feed, 2) The ability of breeders to utilize agricultural and plantation waste has developed, 3). There was a strengthening of the group which had an impact on the creation of an agribusiness area for goat and cattle farming. The achieved targets are then grouped into increasing farmer knowledge in raising cattle and goats intensively. Keywords: Sidorejo, breeders, Umbulsari, Cattle, Goat